Antibacterial activity of methanol crude extracts of marine macro algae from the thikkodi calicut west coast of india - Dr.R.VEERAMOHAN; G. ADAIKALA RAJ, M.; V. VENKATESALU (International Journal of Pharma and Bio Sciences, 2017)
The antibacterial activities of methanol extracts of Caulerpa racemosa (Forsk), Caulerpa sertularioides (Gmelin) Howe, Ulva lactuca Linn, Padina gymnospora (Kutzing) Sonder., Dictyota dichotoma (Hudson) Lamouroux. and Gracilaria multipartita (Clemente) Harvey against bacterial strains viz., Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus mirabilis and Salmonella enterica were studied by using disc diffusion method, determination of MIC and MBC. The methanol extracts of P. gymnospora and D. dichotoma showed the highest antibacterial activity against all the bacterial strains tested. The mean zones of inhibition produced by the extracts in agar disc diffusion assays were from 6.3 to 19.5 mm. The MIC was between 125 and 500 μg/ml and MBC was between 250 and 1000 μg/ml. The highest mean zone of inhibition (19.5 mm) was observed with methanol extract of Padina gymnospora against S. aureus. The lowest MIC (125 µg/ml) and MBC (250 µg/ml) values were observed in methanol extract of P. gymnospora and D. dichotoma against S. aureus. These finding suggest that methanol crude extract of P. gymnospora have potential antibacterial activity.